Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1159/000099005
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotegerin and RANKL Serum Levels and Their Relationship with Serum Ghrelin in Children with Chronic Renal Failure and on Dialysis

Abstract: Background: Osteoprotegerin (OPG) and receptor activator of the nuclear factor ĸB ligand (RANKL) constitute a complex system of mediators involved in the regulation of bone resorption process. Ghrelin, a growth hormone secretagogue, has been shown to modulate proliferation and differentiation of osteoblasts. The present study was carried out to evaluate the serum concentrations of OPG and sRANKL in children with chronic renal impairment (CRI) and on dialysis, and to establish a possible relationship between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 56 publications
2
10
2
Order By: Relevance
“…These findings are in keeping with other studies [23][24][25]. In the total group of uremic patients, total ghrelin levels revealed an inverse correlation with GFR, and multiple regression analysis confirmed GFR as a negative predictor of total ghrelin.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are in keeping with other studies [23][24][25]. In the total group of uremic patients, total ghrelin levels revealed an inverse correlation with GFR, and multiple regression analysis confirmed GFR as a negative predictor of total ghrelin.…”
Section: Discussionsupporting
confidence: 92%
“…Elevated levels of total ghrelin have been demonstrated in children with CKD in three studies [23][24][25], and a negative correlation between total ghrelin and glomerular filtration rate has been shown in CKD children [23]. To the best of our knowledge, acyl ghrelin has been measured in only one pediatric study, which reported unaltered levels [26].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the concentrations found here were substantially higher than the average ghrelin level (about 324-490 pg mL −1 ) found in the plasma of fasting humans, while they were similar to acylated ghrelin levels (about 33-70 pg mL −1 ) in human plasma (Kojima and Kangawa, 2005;Kitamura et al, 2003). It is known that the normal range of ghrelin varies with methodology used (Ozkaya et al, 2007;Kierson et al, 2006). Although it was not among the objectives of the study here, we also found that urine acylated and desacylated ghrelin were 3-and 60-fold higher, respectively, than human plasma ghrelin levels (Kojima and Kangawa, 2005;Groschl et al, 2004).…”
Section: Discussionsupporting
confidence: 52%
“…Increased levels of TG with decreasing GFR have been reported by others (15)(16)(17)(18)(19)21,26) as well as variable removal by dialysis (16,18,21). Some studies reported a decrease in both AG and DG (16,18) by hemodialysis that would not be expected for AG, which is highly bound to large plasma molecules such as lipoprotein (27,28).…”
Section: Discussionmentioning
confidence: 76%